2018
DOI: 10.1177/1740774518796151
|View full text |Cite
|
Sign up to set email alerts
|

Contingency management intervention targeting co-addiction of alcohol and drugs among American Indian adults: Design, methodology, and baseline data

Abstract: This is the first study to examine a culturally tailored contingency management intervention targeting co-addiction of two substances among American Indian adults. By establishing a tribal-university partnership to adapt, implement, and evaluate contingency management, we will increase the literature on evidence-based addiction treatments and research, while improving trust for addiction interventions among American Indian communities through ongoing collaboration. Moreover, results have implications for the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…c RCT = randomized control trial. Ã Quality assessment could not be performed because there was no clearly defined research question(Hong et al, 2018); CBSB = cognitive-behavioral skills building; CPT = cognitive processing therapy; PTSD = post traumatic stress disorder; SCF = Southcentral Foundation; MICRA = motivational interviewing and the community reinforcement approach The majority (n = 11; 61.11%) of the interventions took place in strictly rural or tribal settings(Burduli et al, 2018;Gone and Calf Looking, 2015;Gray et al, 2010;Hanson and Pourier, 2015;Kanate et al, 2015;Kelley et al, 2018;Naquin et al, 2006;Ray et al, 2020;Running Bear et al, 2017;van der Woerd et al, 2010;Venner et al, 2021). Fewer (n = 5; 27.78%) took place strictly in urban contexts…”
mentioning
confidence: 99%
“…c RCT = randomized control trial. Ã Quality assessment could not be performed because there was no clearly defined research question(Hong et al, 2018); CBSB = cognitive-behavioral skills building; CPT = cognitive processing therapy; PTSD = post traumatic stress disorder; SCF = Southcentral Foundation; MICRA = motivational interviewing and the community reinforcement approach The majority (n = 11; 61.11%) of the interventions took place in strictly rural or tribal settings(Burduli et al, 2018;Gone and Calf Looking, 2015;Gray et al, 2010;Hanson and Pourier, 2015;Kanate et al, 2015;Kelley et al, 2018;Naquin et al, 2006;Ray et al, 2020;Running Bear et al, 2017;van der Woerd et al, 2010;Venner et al, 2021). Fewer (n = 5; 27.78%) took place strictly in urban contexts…”
mentioning
confidence: 99%
“…This study was approved by the Washington State University Institutional Review Board and by a Tribal Resolution from the community's Tribal Council. Our study protocol was published previously [26].…”
Section: Study Overviewmentioning
confidence: 99%
“…Alcohol abstinence was defined as ethyl glucuronide (EtG) < 150 ng/ml and analyzed using the ThermoFisher (Waltham, MA, USA) EtG immunoassay on an Indiko benchtop analyzer [22,26]. At study entry a most-used drug was identified.…”
Section: Criteria For Reinforcement For Alcohol and Drug Abstinencementioning
confidence: 99%
See 2 more Smart Citations